Design of a Detachable Type Fish Drier - PILLAI, S AYYAPPAN; PRABHU, P VASUDEVA; BALACHANDRAN, K K (Fishery Technology, 2017)
The paper describes the design of a detachable type fish drier which has been designed to operate on commercial scale. The drier with a raw material capacity of one tonne has been designed after effecting all improvements on the design of the existing tunnel driers available in India. The cost of one drier works out to Rs. 2,16,700/- app.coximately